If it's not what You are looking for type in the equation solver your own equation and let us solve it.
14m-6m-9=39
We simplify the equation to the form, which is simple to understand
14m-6m-9=39
We move all terms containing m to the left and all other terms to the right.
+14m-6m=+39+9
We simplify left and right side of the equation.
+8m=+48
We divide both sides of the equation by 8 to get m.
m=6
| -5v=60 | | 7logb(x)+8logb(z)= | | -4(15+6y)-3y=-6 | | -8x+6=5x+72 | | 5z^2+5z-30=0 | | 4x+17=49 | | ln(x)+ln(16)= | | p=4n+4w | | .8x+7.9=5.9 | | 78=3c+12-6+4 | | 9n^10-10n^9+.75=0 | | (3x-9)(4x+8)=0 | | 3x+16=28 | | 6h=48 | | -2x-2=-9x+47 | | 14x+12=7x+37 | | 6x-15=2x | | 7z^2+7z-42=0 | | 13=x-3 | | 6x-2(x-3)=11(x-2) | | 20x^3-9x^2+1=0 | | y+7=180 | | P^2-21=4p | | -0.5(d-1.2)=2.5 | | -3x-5(-3x+3)=105 | | x*x-2=143 | | (6x+5)(8x^2+7x+4)=0 | | -6=2x-x+4 | | -2(7+11)=6 | | -2(a+3)-9=0 | | y-7=180 | | -5b=-65 |